THE ENERGY RESISTANCE IN INDONESIAN NAVAL TECHNOLOGY COLLEGE STUDENT'S PERSPECTIVE - Andry Gunawan; Suyono Thamrin; Yanif Dwi Kuntjoro (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2022)
Energy security can be understood as a condition to meet the energy needs of the wider community, using the principles of availability, affordability, accessibility, acceptability and sustainability. Indonesia is a country that has enormous potential for energy resources, both fossil energy potential and renewable energy potential. In the current condition, the consumption of energy supply in Indonesia mostly comes from non-renewable energy sources, which if carried out in a sustainable manner will result in reduced reserves of fossil energy sources and contribute to increased greenhouse gas emissions which will lead to changes in the environment. climate globally. Instilling an understanding of the importance of maintaining energy security can be done through educational institutions and outreach to the wider community. One of the educational institutions owned by the Indonesian Navy is STTAL, from the studies conducted by STTAL students there are still few that discuss energy security in the Indonesian Navy. Based on these problems, the researchers wanted to know the perspectives of STTAL students who were analyzed from the knowledge, attitudes and concerns about energy security using a descriptive methodology through a quantitative approach. From this study, it can be seen that the attitudes and concerns of students are already in the high criteria but for knowledge it is still in the medium criteria, so it needs to get further attention. Keywords: energy security, student perspective, knowledge, attitude, concern